2012
DOI: 10.1155/2012/897371
|View full text |Cite
|
Sign up to set email alerts
|

Discrete-State Stochastic Models of Calcium-Regulated Calcium Influx and Subspace Dynamics Are Not Well-Approximated by ODEs That Neglect Concentration Fluctuations

Abstract: Cardiac myocyte calcium signaling is often modeled using deterministic ordinary differential equations (ODEs) and mass-action kinetics. However, spatially restricted “domains” associated with calcium influx are small enough (e.g., 10−17 liters) that local signaling may involve 1–100 calcium ions. Is it appropriate to model the dynamics of subspace calcium using deterministic ODEs or, alternatively, do we require stochastic descriptions that account for the fundamentally discrete nature of these local calcium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 51 publications
1
18
0
Order By: Relevance
“…Our motivation to study the influence of Ca 2þ noise on the IP 3 R arose from the contemporary interest in the stochastic nature of complex Ca 2þ signals (11,20,26,41). Just recently, Thurley et al (13) showed that stimulus intensities of input signals are reliably encoded in stochastic sequences of random spikes, and the body of literature, emphasizing the functional relevance of noise in biological systems, is constantly growing (24,(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our motivation to study the influence of Ca 2þ noise on the IP 3 R arose from the contemporary interest in the stochastic nature of complex Ca 2þ signals (11,20,26,41). Just recently, Thurley et al (13) showed that stimulus intensities of input signals are reliably encoded in stochastic sequences of random spikes, and the body of literature, emphasizing the functional relevance of noise in biological systems, is constantly growing (24,(48)(49)(50)(51)(52).…”
Section: Discussionmentioning
confidence: 99%
“…The influence of Ca 2þ buffers on Ca 2þ signaling has previously been studied, both theoretically (54,(60)(61)(62) and experimentally (63)(64)(65)(66). These studies mainly focused on the influence of mobile and immobile buffers on global Ca 2þ signals, whereas only a very few studies are concerned with the functional role of buffer-dependent Ca 2þ fluctuations (26). The expression profiles for Ca 2þ buffers with widely differing kinetic properties are highly variable among different cell types (35,46).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One important observation is that correlations between the amplitude, duration, and interval-event intervals of simulated Ca 2+ puffs and sparks are strongly influenced by spark termination mechanism (i.e., Ca 2+ -dependent inactivation or stochastic attrition-like). Our formulation can be generalized to account for luminal depletion and/or regulation, both of which known to influence spark termination (Huertas and Smith, 2007), and finite system size effects (Weinberg and Smith, 2012).…”
Section: Discussionmentioning
confidence: 99%